Assessment of the association of ABO blood group in dengue fever diagnosed patient in tertiary care hospital - Kouser, Shaheen; Abbas, Farah Fatima; Naeem Effendi , Fouzia; Huda, Nasrul; Suharwardy Obaid, Munazza; Aman Ali, Humaira; Muhammad Imran; Abdus Salam, Aabiya; Murtaza Ali, Alifya; Nazneen Suri, Mahrukh; Munir, Syeda Fatima (International Journal of Endorsing Health Science Research, 2020)
Background: A serious worldwide medical and public health concern occurs with the dengue virus, which is also an emerging health threat. A victim can be vulnerable and acquire dengue because of his age, genetics, nutritional status, viral strain and secondary infections. Our objective was to identify the ABO blood group system's distribution and relationship in dengue fever (DF) patients. Methodology: The current study has conducted between September 2019 and September 2020 in Dr. Ishrat ul Ebad Institute of Blood Diseases Department. The research work was viewed and accepted by the ethics and research committees. Case records of patients with blood systems and their relation among dengue nonstructural protein 1 (NS1) antigen /dengue immunoglobulin M (IgM) and immunoglobulin G (lgG) were included in this study. Results: Among 204 cases, 82 were blood group O positive, 59 were B positive, 38 were A positive, 16 were AB positive, 4 were O negative, and 2 were blood group A negative. The association of the ABO blood group with dengue was statistically significant (p=0.046). Blood group O+ has the highest number of cases, 66 (42.9 %), than controls, 16 (32 %). Conclusion: This study overall consummates that blood group O is linked with a greater possibility of acquiring DF in comparison with different other blood group types. There is a significant relationship between blood group and DF observed.